The 2020 Vision for food, agriculture, and the environment in South Asia: continuing the dialogue - Gunatilleke, Godfrey (International Food Policy Research Institute, 1998)
In June 1998 IFPRI and the Marga Institute organized a 2020 South Asia workshop in Colombo to continue the dialogue begun in a 2020 South Asia workshop in Kathmandu in March 1995. The meeting in Colombo revisited the 2020 Vision for South Asia in light of the major economic developments of recent years inside and outside the region. G. L. Pieris, the Sri Lankan minister of justice, constitutional affairs, ethnic affairs, and national integration, inaugurated the workshop. About 40 researchers, technical experts, and policymakers from 5 South Asian countries participated in the meeting. The objectives and strategies are those agreed upon by the workshop participants. Projections by the International Food Policy Research Institute (IFPRI) indicate that even with an annual average rate of economic growth of 5.5 percent during the next two decades and substantial investment in health and education, South Asia will still have about 70 million malnourished children by 2020. Food insecurity and poverty will continue to affect about 200 million people. If economic growth drops below the projected level by about 25 percent, the region is unlikely to see any reduction in malnutrition and poverty. In such conditions, social and political tensions could reach proportions that governments might find difficult to manage in an orderly manner. With these concerns in mind, workshop participants addressed the following issues: The realistic goals that countries should set to eradicate food insecurity, poverty, and malnutrition and ensure a reasonably high quality of life by 2020; The combination of strategies that would enable countries to manage their natural resources on a sustainable basis while achieving the goals set for 2020; The improvements and changes in policy that should have high priority for the purpose of achieving these goals; and The main areas of regional cooperation for realizing the goals.